Poverty eradication in Bangladesh and recent concern over context Covid-19: A sociological analysis - Farzana, Raka; Ilias, Muhammad (Eximia, 2021)
Poverty in Bangladesh, like in many other developing countries, has been a serious social concern for a long time. Approximately 90% of the population lived in poverty shortly after the country’s independence. Bangladesh has made significant progress since early 1990s economic reforms and trade liberalization, as well as increased economic growth during the early 2000s.The remarkable progress has been recognized by international institution. Bangladesh’s per capita has increased almost threefold between 2010 and 2020. Bangladesh is projected to eliminate extreme poverty by 2021, the first country in South Asia to do so. But the unfortunate intrusion of COVID19 has disturbed the whole plan in Bangladesh. Strategic and effective planing in this regard is required.This paper is a discussion of the scenerio using various secondary data and Sociological insight.